Modelling the causal linkages among residential electricity consumption, gross domestic product, price of electricity, price of electric appliances, population and foreign direct investment in Malaysia - Ivy-Yap L.L.; Bekhet H.A. (Inderscience Publishers, 2023)
cointegration analysis; dynamic response; electricity supply; foreign direct investment; Granger causality test; Gross Domestic Product; multivariate analysis; price determination; Malaysia